The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.33594/000000358
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Hot and Spicy: TRPV Channels and their Pharmacological Modulation

Abstract: Transient receptor potential vanilloid (TRPV) channels are part of the TRP channel superfamily and named after the first identified member TRPV1, that is sensitive to the vanillylamide capsaicin. Their overall structure is similar to the structure of voltage gated potassium channels (Kv) built up as homotetramers from subunits with six transmembrane helices (S1-S6). Six TRPV channel subtypes (TRPV1-6) are known, that can be subdivided into the thermoTRPV (TRPV1-4) and the Ca2+-selective TRPV channels (TRPV5, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 141 publications
0
12
0
Order By: Relevance
“…Besides R557, residues Y511 and S512 from S3 segment, and M547 and T550 from S4 segment, are also essential for agonistic effect of capsaicin as mutations Y511A or S512Y of rTRPV1 abolish the channel sensitivity to capsaicin. This indicates that these key residues also contribute to CPIPC -mediated activation of TRPV1 [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides R557, residues Y511 and S512 from S3 segment, and M547 and T550 from S4 segment, are also essential for agonistic effect of capsaicin as mutations Y511A or S512Y of rTRPV1 abolish the channel sensitivity to capsaicin. This indicates that these key residues also contribute to CPIPC -mediated activation of TRPV1 [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The need to find new therapeutic strategies must be oriented to a complete identification of the involved receptors. TRPV receptors are involved in a plethora of physiological and pathological conditions, which makes them promising pharmacological targets [33]. Some doubts remain about the feasibility of administering specific TRPV1 agonists and antagonists in vivo due to the high probability to induce side effects as a consequence of their wide distribution in different cells and tissues [19].…”
Section: Discussionmentioning
confidence: 99%
“…TRPV channels in the CNS play a great role not only in pain but also in neuropsychiatric disorders, such as depression, stress, and anxiety ( Singh et al, 2019 ). It was found that all kinds of tissues and organs with TRPV channels expression contribute to a plethora of physiological or pathophysiological effects ( Seebohm and Schreiber, 2021 ).…”
Section: Transient Receptor Potential Vanilloid Channelsmentioning
confidence: 99%